Antimicrobial and ultrastructural properties of root canal filling materials exposed to bacterial challenge. (February 2020) - Long, J; Kreft, JU; Camilleri, J
Abstract: Introduction: Chemo-mechanical preparation of the root canal leaves behind viable bacteria which can lead to treatment failure. Materials used inside the root canal should possess antimicrobial properties and also resist disintegration in the presence of biofilm. Methods: Gutta-percha, three root canal sealers (Pulp Canal Sealer, AH Plus and BioRoot RCS) and materials used to make posts (a metal and a resin) were evaluated. Their antimicrobial activity against Enterococcus faecalis in direct contact was assessed by scanning electron microscopy and live-dead staining using confocal microscopy over a period of eight weeks. The materials' structural integrity was assessed by scanning electron microscopy. Results: The antimicrobial activity of the materials varied. The metal alloy posts as well as BioRoot RCS sealer did not allow any biofilm accumulation; but gutta-percha, Pulp Canal Sealer and resin from fibre-reinforced posts encouraged thick biofilm accumulation. Microstructural changes were observed in AH Plus (washout) and BioRoot (crystal deposition) in contact with biofilm. The Pulp Canal and BioRoot RCS sealers exhibited a modified ion leaching pattern in contact with microbially loaded media. Conclusions: The microbial challenge affected the material microstructure in some of the materials tested and allowed biofilm accumulation. Although clinical success depends on a number of factors, materials that are structurally sound and exhibit antimicrobial properties are preferable for endodontic therapy and tooth restoration involving entry in the root canal.